(untitled) (Fiep Bulletin - online, 2014)
This article is a result of a survey of about nine months of pathologies postural students in the School Hall Kazuko Inoue-Child Education and Education Foundation, which is located in Vila Colonel Claudius, District of Uvaranas, in the municipality of Ponta Grossa / State of Parana. They were assessed 210 students in the age group of 08 to 10 years of both sexes. The primary purpose beyond the lifting of postural disorders, also was the realization that some children have two or more disorders at the same time, as evidenced by this coefficient of variation found in 69.97%, considered by the statistical literature as a high value.